2022
DOI: 10.1111/bjet.13272
|View full text |Cite
|
Sign up to set email alerts
|

Share and embrace demographic and location diversity: Creating an Instagram‐based inclusive online learning community

Abstract: It is critical to create an inclusive online learning environment for students with diverse demographic information studying in different environments, especially during the COVID‐19 pandemic when they are disconnected from peers. Guided to create an inclusive online learning community by situated learning theory and community of practice, both of which advocate learning in context and community, we invited 115 undergraduate students to post photos related to environmental psychology concepts and their surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Interdisciplinary studies have demonstrated, however, that there is often a discrepancy between political intentions to design public policies and what occurs during their implementation [6,8,26,28,36]. The literature suggests that while systems and structures can be designed to be inclusive, the empirical outcome depends on how values, beliefs, and attitudes of powerful organizational members welcome and implement the change in practice [8,14,28].…”
Section: Accessibility and Affordability In Archetype Theorizingmentioning
confidence: 99%
“…Interdisciplinary studies have demonstrated, however, that there is often a discrepancy between political intentions to design public policies and what occurs during their implementation [6,8,26,28,36]. The literature suggests that while systems and structures can be designed to be inclusive, the empirical outcome depends on how values, beliefs, and attitudes of powerful organizational members welcome and implement the change in practice [8,14,28].…”
Section: Accessibility and Affordability In Archetype Theorizingmentioning
confidence: 99%
“…During COVID-19, due to the lockdown and the transformation to online learning, students' learning environments are constrained as physical learning environments like campus are not accessible to students. Since learners are away from conventional classrooms and campus, the potential loss of environment/situation awareness and sense of belonging becomes a key concern for both students and instructors (Zhu et al, 2022).…”
Section: Situated Learning Environments Through Mobile Social Mediamentioning
confidence: 99%
“…The third paper by Zhu et al (2022) attempts to expand the scope of inclusive education by introducing physical learning environments that encourage students to express their identities by sharing online posts using mobile social networks in an environmental psychology course. The study supports students to share, discuss, and build knowledge from different perspectives and diverse contexts, and to build their sense of belonging.…”
Section: Papers In This Special Sectionmentioning
confidence: 99%